2021
DOI: 10.3233/ch-201078
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory iron chelator, DIBI, reduces leukocyte-endothelial adhesion and clinical symptoms of LPS-induced interstitial cystitis in mice

Abstract: BACKGROUND: Interstitial cystitis (IC) is a prevalent and debilitating chronic inflammatory disease of the urinary bladder. Currently there are no fully effective therapeutic agents available, in part due to the still obscure pathogenesis of IC. Lipopolysaccharide (LPS) also known as endotoxin from Gram negative bacteria elicits IC in mice and has formed the basis of model systems for investigation. Excess free iron plays an important role in inflammation through generation of reactive oxygen species (ROS). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Berger et al found intravesical LPS administration to be superior at increasing adhesion when compared to intraperitoneal LPS administration [49]. The other studies examined exclusively used intravesical administration for LPS [6,47]. This is consistent with work comparing intravesical and intraperitoneal LPS administration in rats.…”
Section: Resultssupporting
confidence: 60%
See 3 more Smart Citations
“…Berger et al found intravesical LPS administration to be superior at increasing adhesion when compared to intraperitoneal LPS administration [49]. The other studies examined exclusively used intravesical administration for LPS [6,47]. This is consistent with work comparing intravesical and intraperitoneal LPS administration in rats.…”
Section: Resultssupporting
confidence: 60%
“…Interestingly, both groups used the same method for intravesical LPS administration: 150 µg/mL of LPS in 50 µL of saline held in the bladder for 30 min. They also both used FITC-albumin for visualization of the capillary beds, and both began imaging two hours after LPS administration [6,49]. [6]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although DIBI has been shown to have therapeutic effects in local and systemic inflammatory models [11][12][13][14][15], the molecular mechanisms involved in these effects have yet to be fully understood. Therefore, we established an experimental ALI model in mice by using intranasal endotoxin administration at a dosage of 5 mg/kg LPS and aimed to study the effects of DIBI at several treatment timepoints post LPS administration.…”
Section: Discussionmentioning
confidence: 99%